The Curriculum of Early Childhood Education: Indonesia and United Kingdom - Husein, Saddam (Pendidikan Agama Islam, 2020)
This paper aims to investigate the curriculum of early childhood education in Indonesia and the United Kingdom (UK) and how they pertain to each other. Library research was conducted to gather information intended. The findings confirm that the curriculum of early childhood education in Indonesia applies curriculum 2013 which consists of aspect development of curriculum structure, and the learning process with a scientific approach. While the UK applies the curriculum according to the statutory Early Years Foundation Stage (EYFS) framework which recognizes the importance of play and a balance of adult-led and child-initiated activities. Moreover, there is a basic difference between these two curriculum aspects, which Indonesia includes the religious and moral values to the body of the curriculum, while the UK does not. However, both Indonesia and UK are closely similar which promotes a balance between the development of academic and literacy skills, socio-emotional development, and creative and physical development.